Values in management: cultural restructure for an effective performance appraisal - Abdullah, Fadzilah (2015)
The world of business has changed significantly. Human resources management (HRM) now has become part of the organization’s strategic decision making process, where human capital is becoming the core of a firm’s ability to achieve superior performance. The competitive edge of an organization exists within the quality of its people. Since literatures have proven that values affect human behaviour, enriching organizational environment and an alignment of individual values with organizational values is important in order to have a long term organization’s sustainability. The existing system of beliefs and values that shaped the model for management now is seems to be not effective enough for the current management environment. The purpose of this conceptual paper is to clarify the concept of values in management from the perspective of human resources. This paper discusses the need to primarily shift from an existing system of employees to value based management. This new approach of leadership tool will be discussed from HRM perspective and will be proposed to be improved in the area of performance appraisal. A survey of literatures from relevant fields is carried out to justify the main issue related to the relationship between values and the effective performance appraisal. This paper proposed an integrated conceptual framework of effective performance appraisal by testing values as the mediating effect of values in management in the context of HRM perspective for further empirical work.